2022
DOI: 10.1088/1757-899x/1225/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Rod Shaped ZnO using Extract of Origanum majorana Leaf and Investigation for Antibacterial Applications

Abstract: In this research article, we have fabricated the zinc oxide (ZnO) nanoparticles (NPs) with help of aqueous extract of leaf of Origanum majorana and studied their antimicrobial activity. Origanum majorana is one of medicinally important plant of Lamiaceae/Labiatae family. Green-approach of NPs has been favoured over traditional synthesis methods, as plant-based extracts have phytochemicals, which are non-toxic and biologically safe. The phytochemicals such as flavonoids, derivatives of phenol and polyphenolic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…According to Vijayakumar et al [126], this is due to G− having an outer lipopolysaccharide membrane surrounding their thin peptidoglycan cell wall making it difficult for NPs to penetrate the cells. Saini and associates [123] also observed a greater antibacterial activity of Origanum majorana-mediated ZnO NPs against the G+ S. aureus and Streptococcus pneumonia (S. pneumonia) bacteria compared to the G− Pseudomonas aeruginosa (P. aeruginosa) and the E. coli bacteria and using the broth diffusion method. The MICs were reported to be 100-125 µg/mL for E. coli, 150-175 µg/mL for P. aeruginosa, and 76-100 µg/mL for both S. aureus and S. pneumonia.…”
Section: Antibacterial Activity Of Lamiaceae-mediated Zno Npsmentioning
confidence: 93%
“…According to Vijayakumar et al [126], this is due to G− having an outer lipopolysaccharide membrane surrounding their thin peptidoglycan cell wall making it difficult for NPs to penetrate the cells. Saini and associates [123] also observed a greater antibacterial activity of Origanum majorana-mediated ZnO NPs against the G+ S. aureus and Streptococcus pneumonia (S. pneumonia) bacteria compared to the G− Pseudomonas aeruginosa (P. aeruginosa) and the E. coli bacteria and using the broth diffusion method. The MICs were reported to be 100-125 µg/mL for E. coli, 150-175 µg/mL for P. aeruginosa, and 76-100 µg/mL for both S. aureus and S. pneumonia.…”
Section: Antibacterial Activity Of Lamiaceae-mediated Zno Npsmentioning
confidence: 93%
“…These nanoparticles demonstrate enhanced biocompatibility and exhibit favorable responses when interacting with biological tissue, resulting in improved performance. Consequently, there is an abundance of literature available that extensively explores the diverse bio-medical applications of ZnO-NPs, as depicted in Figure 6 [3,4,52,59].…”
Section: Zinc Oxide Nanoparticles Bio-medical Applicationsmentioning
confidence: 99%
“…Additionally, studies have demonstrated that ZnO-NPs synthesized by O. majorana extract display antibacterial and antifungal activity against E.coli, K.pneumoniae, Salmonella typhimurium, Enterobacter cloacae, and P. aeruginosa. Saini et al [59] conducted a study to investigate the antibacterial and fungi activity of ZnO-NPs using O. majorana leaf aqueous extract. The results showed that these ZnO-NPs exhibited strong bactericidal activity against S. aureus, P. aeruginosa, E. coli, and S. pneumoniae.…”
Section: Antibacterial Action Of Zno-npsmentioning
confidence: 99%
“…and Origanum majorana leaf extract (379.75 nm) (18,23). The UV-vis band of ZnO NPs containing Calendula officinalis flower extract exhibited a peak at 355 nm using the green synthesis method (17).…”
Section: Antioxidant Activity Of Zinc Oxide Nanoparticlesmentioning
confidence: 99%